Impact of Obesity Caused by a High-Fat Diet on the Heart’s Redox Balance - Yildy Utreras-Mendoza; Isidora Mujica Valenzuela; Luis Montecinos; Paulina Donoso; Gina Sánchez (Antioxidants, 2025)
Obesity has been implicated in the induction of oxidative stress, which is thought to contribute to the pathogenesis of various cardiovascular diseases, including cardiac hypertrophy. However, the redox status during the early stages of cardiac hypertrophy remains inadequately characterized. In this study, we administered a high-fat diet (HFD) to C57BL/6N mice for 12 weeks. We investigated the expression of biomarkers associated with hypertrophy and oxidative stress, including lipid peroxidation, protein carbonylation, and the redox couples NADH/NAD+, NADPH/NADP+, and GSH/GSSG. Additionally, we assessed the expression levels and enzymatic activities of catalase, glutathione peroxidase, glutathione reductase, and superoxide dismutase. Following 12 weeks on a HFD, mice exhibited obesity and a 10% increase in the heart weight/tibia length ratio, together with an upregulation in the mRNA levels of β-myosin heavy chain, brain natriuretic peptide, and regulator of calcineurin 1, isoform 4. There was also a significant increase in NOX4 content in the heart of these animals; however, we observed no rise in protein carbonylation and a decrease in lipid peroxidation products. As for the redox couples, the GSH/GSSG ratio nearly doubled, while the NADH/NAD+ and NADPH/NADP+ ratios remained stable. All antioxidant enzyme mRNAs examined showed increased expression; however, only glutathione reductase showed higher activity. Our findings suggest that reductive stress is predominant within the cardiac environment of these animals.